BIOFILTRATION KINETICS OF TOFU INDUSTRY WASTEWATER USING OF ZEOLITE MEDIUM - Rodiyanti, Rodiyanti; Triyono, Sugeng; Haryono, Nugroho (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2015)
This researchwas aimed to investigate reactionkinetic of tofu industrywastewater using zeolitemedium. A static filter reactor using zeolitemediumwas constructed to carry out this research. Tofuwastewaterwas resirculated through themedium with various hydraulic retention times (HRT): 0, 3, 6, 12, 24, 36, and 48 hours. First order reactionwas then applied on this kinetics. The results showed that pHincreased from4.1 to 8.02. Total P in the wastewater decreased from12,1mg/L to 6,91mg/L (42%reduction),while in themedia totalP increased from 3,04 mg/L to 5,97 mg/L within 48 hours of filtration. N-NH4 + decreased from 64.184 mg/L to 12.85 mg/L (79.9%reduction). Total Solids decreased from 10.404mg/L to 4003m(61.5%reduction).